2017
DOI: 10.3390/nu9040372
|View full text |Cite
|
Sign up to set email alerts
|

The Diet and Haemodialysis Dyad: Three Eras, Four Open Questions and Four Paradoxes. A Narrative Review, Towards a Personalized, Patient-Centered Approach

Abstract: The history of dialysis and diet can be viewed as a series of battles waged against potential threats to patients’ lives. In the early years of dialysis, potassium was identified as “the killer”, and the lists patients were given of forbidden foods included most plant-derived nourishment. As soon as dialysis became more efficient and survival increased, hyperphosphatemia, was identified as the enemy, generating an even longer list of banned aliments. Conversely, the “third era” finds us combating protein-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 287 publications
(307 reference statements)
0
38
1
1
Order By: Relevance
“…Recently, several studies reported that nutritional status was closely associated with morbidity and mortality in chronic HD patients . Therefore, convenient and objective tools such as CI and GNRI facilitate timely and serial assessment of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies reported that nutritional status was closely associated with morbidity and mortality in chronic HD patients . Therefore, convenient and objective tools such as CI and GNRI facilitate timely and serial assessment of nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported that nutritional status was closely associated with morbidity and mortality in chronic HD patients. 10,11 Therefore, convenient and objective tools such as CI and GNRI facilitate timely and serial assessment of nutritional status. In this study, CI facilitated the differential diagnosis of chronic HD patients with normal nutritional status from HD patients with malnutrition when tracked over a period of 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Most scoring systems for malnutrition use parameters that might be less reliable or less representative in patients on dialysis, and their relation with mortality in this population might be counterintuitive. The most striking example is the obesity paradox that higher BMI appears to be protective in patients on dialysis [5]. Therefore, it is essential that malnutrition scores are validated in dialysis patients, using mortality as outcome.…”
Section: Plos Onementioning
confidence: 99%
“…Malnutrition is an important and prevalent problem affecting 16% to 70% of dialysis patients, depending on the study population and assessment procedure [1][2][3]. In dialysis patients, insufficient nutritional intake, compromised clinical well-being, comorbidity and dialysis related factors can lead to poor nutritional status [4][5][6]. Poor nutritional status is on its turn associated with impaired functional capacity, increased risk of complications, lower quality of life and limited survival [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Is phosphate restriction harmful?There is a concern that phosphate restriction may result in worse outcomes (43)(44)(45)(46). Previously, phosphate restriction placed more emphasis on protein restriction, which may lead to malnutrition, and an even worse prognosis, since malnutrition results in high mortality in hemodialysis patients (47). Therefore, we should instead consider reducing phosphate intake without restriction of protein consumption.…”
Section: Possible Measures To Reduce Phosphate Burdenmentioning
confidence: 99%